Hawk Ridge : Minnesota's Birds of Prey - Erickson, Laura (Book collections on Project MUSE., 2012)
Was Caesar like the eagle because of his aquiline (from aquila, "eagle" in Latin) nose, or does the eagle seem imperial because of his Caesar-like beak? Does the sharp vision of a "hawk-eyed" observer have any basis in nature? And what the heck is "kettling" to a bird-watcher-or, for that matter, a bird? Raptors have captured the imagination from time immemorial and have an especially rich history in Minnesota. The ancient peoples whose pictographs adorn the rock faces of Lake Superior's North Shore may well have witnessed the first hawk movements along Lake Superior-the same annual migration.